Double‐Layer Nacre‐Inspired Polyimide‐Mica Nanocomposite Films with Excellent Mechanical Stability for LEO Environmental Conditions. Issue 2 (21st November 2021) - Pan, Xiao‐Feng; Wu, Bao; Gao, Huai‐Ling; Chen, Si‐Ming; Zhu, YinBo; Zhou, LiChuan; Wu, HengAn; Yu, Shu‐Hong
Abstract: Owing to their outstanding comprehensive performance, polyimide (PI) composite films are widely used on the external surfaces of spacecraft to protect them from the adverse conditions of low Earth orbit (LEO). However, current PI composite films have inadequate mechanical properties and atomic oxygen (AO) resistance. Herein, this work fabricates a new PI‐based nanocomposite film with greatly enhanced mechanical properties and AO resistance by integrating mica nanosheets with PI into a unique double‐layer nacre‐inspired structure with a much higher density of mica nanosheets in the top layer. In addition, the unique microstructure and the intrinsic properties of mica also impart the nanocomposite film with favorable ultraviolet and high‐temperature resistance. The comprehensive performance of this material is superior to those of pure PI, single‐layer PI‐mica, and previously reported PI‐based composite films. Thus, the double‐layer nanocomposite film displays great potential as an aerospace material for use in LEO. Abstract : A polyimide‐mica (PI‐Mica) nanocomposite film with outstanding mechanical properties and atomic oxygen resistance is produced by integrating mica nanosheets with polyimide into a double‐layer nacre‐inspired structure with a much higher density of mica in the top layer. This unique microstructure and advantages of mica also impart the film with favorable resistance to ultraviolet, space debris, and high temperatures.